The Blueness of the Evening : Selected Poems of Hassan Najmi - Najmī, Ḥasan (Book collections on Project MUSE., 2018)
This selection of Hassan Najmi's poems, translated by Mbarek Sryfi and Eric Sellin, provides an excellent introduction to the work of one of Morocco's foremost poets and to a school of modern verse emerging in the Arab World. Scenes of late night cityscapes, lonely interiors, awe-inspiring desert wastes, and seaside vistas are found within the exquisitely subtle lyric moods and nuances of Najmi's ars poetica, providing insight into the geographical, political, and linguistic ferment that have made Morocco an exciting hub of creative activity in the twenty-first century.